2022
DOI: 10.1038/s41598-022-26289-6
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of submacular hemorrhage secondary to age-related macular degeneration with subretinal injection of air and tissue plasminogen activator

Abstract: Submacular hemorrhage (SMH) can lead to devastating visual loss in patients with age-related macular degeneration. We retrospectively evaluated the surgical outcomes of vitrectomy with subretinal injection of tissue plasminogen activator, bevacizumab, and air in 13 cases. Visual prognosis, anatomical results obtained with optical coherence tomography (OCT), and their correlations were investigated. We analyzed OCT parameters including SMH height, pigment epithelial detachment (PED) height and width, and status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Martel et al [43, 44] reported a surgical technique of adding subretinal air in addition to subretinal tPA air to facilitate displacement of SRH. With this technique, subretinal air is expected to localize at the submacular space above subretinal fluid due to its buoyancy, thus protecting the macula from being reoccupied by the original hemorrhage.…”
Section: Surgical Approaches For Srh Management In Amdmentioning
confidence: 99%
“…Martel et al [43, 44] reported a surgical technique of adding subretinal air in addition to subretinal tPA air to facilitate displacement of SRH. With this technique, subretinal air is expected to localize at the submacular space above subretinal fluid due to its buoyancy, thus protecting the macula from being reoccupied by the original hemorrhage.…”
Section: Surgical Approaches For Srh Management In Amdmentioning
confidence: 99%
“…There are several treatment methods for SMH. Non-vitrectomy treatments, including intravitreal injection of gas, alteplase (tPA), and anti-vascular endothelial growth factor (VEGF) drugs, have some good results; however, the treatment results are not ideal when a large SMH occurs [9][10][11]. Vitrectomy combined with mechanical removal of subretinal hemorrhage and blood clots can lead to certain complications such as retinal detachment, proliferative vitreoretinopathy, mechanical retinal injury, and retinal tears, and have an impact on patient prognosis.…”
mentioning
confidence: 99%